KONTRIBUSI MINAT BELAJAR DAN GAYA BELAJAR TERHADAP HASIL BELAJAR MELAKUKAN INSTALASI PERANGKAT JARINGAN LOKAL (LAN) SISWA KELAS 1 TKJ SMK NEGERI 1 LHOKSUKON - Erry Furqan; Kasman Rukun; Yusri Abdul Hamid (Universitas Negeri Padang, 2016)
This Research background is still many students in class 1 TKJ obtaining result of learning below KKM, although flatten of class have exceeded KKM skor at the subject of Installation Peripheral of Local Area Network (LAN).The specified KKM in the school is ≥ 70,00 with the spanned 0 - 100. The purpose of this research is to express there are any contribution between enthusiasm learn and style learn to result of learning outcame of subject Installation Peripheral of Local Area Network ( LAN) Class 1 SMKN 1 Lhoksukon. Type of this research is descriptive korelasional. Type of the data in this research is primary and sekunder data. Primary data obtained data direct from responden concerning enthusiasm learn and style learn, while data of sekunder is students learning outcomes obtained from a teacher Installation Peripheral of Local Area Network ( LAN). Population in this research is 83 students class 1 TKJ SMKN 1 Lhoksukon that divided into two class. Technique to take a sampel in this research is random sampel technique by using formula of Taro Yamane obtained sampel counted 46 students. Data analysed by using program of SPSS ( Statistic Product Service Solution and) version 16.0. from result of this research got (1) Enthusiasm Learn (X1) give contribution to result learning outcome 28,94%.(2) Style Learn (X2) give contribution to result learning outcome 16,97% and (3) Level of pesentase of enthusiasm variable contribution learn (X1) and style learn (X2) collectively together is 33,64%. It can be concluded that Enthusiasm Learn and Style Learn give contribution to learning outcome, if students enthusiasm learn and style learn is high learning outcome will be increase. Keyword : Contribution, enthusiasm learn, style learn, learn outcome of subject Installation peripheral of local Area network ( LAN)